Violence While in Utero: The Impact of Assaults during Pregnancy on Birth Outcomes - Currie, Janet; Mueller-Smith, Michael; Rossin-Slater, Maya (The Review of Economics and Statistics, 2022)
We study the effects of prenatal exposure to violent crime on infant health, using New York City crime records linked to mothers' addresses in birth records data. We address endogeneity of assault exposure with three strategies and find that in utero assault exposure significantly increases the incidence of adverse birth outcomes. We calculate that the annual social cost of assault during pregnancy in the United States is more than $3.8 billion. Since infant health predicts long-term wellbeing and disadvantaged women are disproportionately likely to be domestic abuse victims, violence in utero may be an important channel for intergenerational transmission of inequality.